The relationship between parent–child relationship and peer victimization: a multiple mediation model through peer relationship and depression - Zhou, Pingyan; Dong, Jinqi; Liu, Jian; Wen, Hongbo; Wang, Zhe (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Peer victimization is a highly prevalent worldwide issue with cross-cultural characteristics. Parent-child relationship and peer victimization is known to be interrelated, but how they influence each other remains unclear. This study explored the mechanisms of peer victimization related to parent-child relationship.Methods: A total of 58,756 fourth grade students aged 10-12 years (10.83 ± 0.83, 54.4% males) from China completed four questionnaires. A multiple mediator model was tested, in which the two variables influenced each other through the mediating factors of peer relationship and depression.Results: Peer victimization was indirectly negatively impacted by parent-child relationship through two chain mediating factors of peer relationship and depression: 1) the mediational path through peer relationship with an effect size of 44.66%; 2) the mediational path through depression with an effect size of 21.64%; and 3) the mediational path through peer relationship and depression with an effect size of 18.08%. The total mediational effect size was 84.11%.The effect size through peer relationship is the strongest among the three mediation paths, suggesting that peer relationship is the key determinant in breaking the link between parent-child relationship and victimization. Poor parent-child and peer relationships may be risk factors eliciting peer victimization. Compared to internalizing behaviors (e.g., depression), low-quality interpersonal relationships maybe the root cause of the formation and maintenance of victimization. Thus, intervention programs against bullying should pay more attention on children's contextual factors, especially their relationships with their families and peers, among children at an early age.